2020
DOI: 10.21203/rs.2.23449/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Perceptions and experiences of men and women towards acceptability and use of contraceptives in underserved areas of Karachi, Pakistan: A Midline Qualitative Assessment of Sukh Initiative, Karachi Pakistan

Abstract: Background: Family planning (FP) is an essential component of Sustainable Development Goals (SDG) and contributes directly to SDG targets 3.7 and 5.6. In Pakistan, contraceptive use has remained stagnant over the past 5 years. This change has been very slow when compared to the FP2020 pledge. The Sukh initiative project was conceived and implemented to alleviate these challenges by providing access to quality contraceptive methods in some underserved areas of Karachi, Pakistan. A qualitative study was conducte… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Ali & White, 2005;Asif, Pervaiz, Afridi, Abid, & Lassi, 2021;Douthwaite & Ward, 2005;Fikree, Razzak, & Durocher, 2005;Kiani, 2003;Mahmood & Ringheim, 1996;Mubarik, Jameel, & Khalil, 2016;R. Mustafa, Afreen, & Hashmi, 2008;Naqvi, Hashim, Zareen, & Fatima, 2011;Nasir, Tahir, & Zaidi, 2010;Raheel, Karim, Saleem, & Bharwani, 2012;Sajid & Malik, 2010;Saleem et al, 2020;Siddiqui et al, 2020;Stephenson & Hennink, 2004a). According to all of these studies, education plays a vital role in making family planning decisions.…”
Section: Drivers Of Family Planning Services Utilization In Pakistan:...mentioning
confidence: 99%
See 2 more Smart Citations
“…Ali & White, 2005;Asif, Pervaiz, Afridi, Abid, & Lassi, 2021;Douthwaite & Ward, 2005;Fikree, Razzak, & Durocher, 2005;Kiani, 2003;Mahmood & Ringheim, 1996;Mubarik, Jameel, & Khalil, 2016;R. Mustafa, Afreen, & Hashmi, 2008;Naqvi, Hashim, Zareen, & Fatima, 2011;Nasir, Tahir, & Zaidi, 2010;Raheel, Karim, Saleem, & Bharwani, 2012;Sajid & Malik, 2010;Saleem et al, 2020;Siddiqui et al, 2020;Stephenson & Hennink, 2004a). According to all of these studies, education plays a vital role in making family planning decisions.…”
Section: Drivers Of Family Planning Services Utilization In Pakistan:...mentioning
confidence: 99%
“…Studies showed the positive relationship among female's decision-making power and the usage of family planning methods (Douthwaite & Ward, 2005;Fikree et al, 2005;Mahmood & Ringheim, 1996;G. Mustafa et al, 2015;Naqvi et al, 2011;Nasir et al, 2010;Saleem et al, 2020;Stephenson & Hennink, 2004b).…”
Section: Drivers Of Family Planning Services Utilization In Pakistan:...mentioning
confidence: 99%
See 1 more Smart Citation